A contingent valuation study on fear of crime in Singapore - Chiou, Zi Lin (Nanyang Technological University, 2024)
This paper examines the fear of crime in Singapore to enhance future Cost-Benefit Analysis (CBA) studies on rehabilitation programmes. Using a contingent valuation (CV) method, the study quantifies Singaporeans’ willingness to pay (WTP) to reduce three types of crimes: murder, theft, and cybercrime and scams. 254 respondents were surveyed. The findings show a collective WTP of S$163.70 million for murder, S$61.36 million for theft, and S$88.08 million for cybercrime and scams. This study expands beyond demographic factors – such as age, income, and ethnicity – to study how contextual factors such as social and informal social controls, environment, sense of safety and exposure to mass media affect Singaporeans’ WTP. Our findings corroborate existing findings that demographic factors have a significant influence on Singaporeans’ WTP. However, contextual factors were found to be insignificant, perhaps due to a sense of safety that has been taken for granted. Our findings indicate that policy measures to address the public’s fear of crime would be more effective in targeting families and the elderly population. Finally, our findings also indicate that rehabilitation programmes in Singapore can be better redesigned to address the fears of specified population segments.